Ethylene Mediates Alkaline-Induced Rice Growth Inhibition by Negatively Regulating Plasma Membrane H+-ATPase Activity in Roots - Chen, Haifei; Zhang, Quan; Cai, Hongmei; Xu, Fangsen (Frontiers in Plant Science, 2017)
pH is an important factor regulating plant growth. Here, we found that rice was better adapted to low pH than alkaline conditions, as its growth was severely inhibited at high pH, with shorter root length and an extreme biomass reduction. Under alkaline stress, the expression of genes for ethylene biosynthesis enzymes in rice roots were strongly induced by high pH and exogenous ethylene precursor ACC and overproducing ethylene in etol1-1 mutant aggravated the alkaline stress-mediated inhibition of rice growth, especially for the root elongation with decreased cell length in root apical regions. Conversely, ethylene perception antagonist silver (Ag+) and ein2-1 mutants could partly alleviate the alkaline-induced root elongation inhibition. The H+-ATPase activity was extremely inhibited by alkaline stress and exogenous ACC. However, the H+-ATPase-mediated rhizosphere acidification was enhanced by exogenous Ag+, while H+ efflux on the root surface was extremely inhibited by exogenous ACC, suggesting that ethylene negatively regulated H+-ATPase activity under high-pH stress. Our results demonstrate that H+-ATPase is involved in ethylene-mediated inhibition of rice growth under alkaline stress.